2017
DOI: 10.1016/j.ccell.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

LMO1 Synergizes with MYCN to Promote Neuroblastoma Initiation and Metastasis

Abstract: Summary A genome-wide association study identified LMO1, which encodes a LIM-domain-only transcriptional cofactor, as a neuroblastoma susceptibility gene that functions as an oncogene in high-risk neuroblastoma. Here we show that dβh promoter-mediated expression of LMO1 in zebrafish synergizes with MYCN to increase the proliferation of hyperplastic sympathoadrenal precursor cells, leading to a reduced latency and increased penetrance of neuroblastomagenesis. The transgenic expression of LMO1 also promoted hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 58 publications
7
81
0
Order By: Relevance
“…MYCN is involved in cell proliferation, apoptosis, survival and differentiation (62). Neuroblastoma models in which MYCN is overexpressed in the neural crest lead to neuroblastoma tumor development, that is accelerated by cooperation with other oncogenes and tumor suppressor genes, such as ALK, NF1, TP53, LIN28B and LMO1, driving increased penetrance and earlier onset of neuroblastoma (63)(64)(65)(66)(67)(68). Other factors, which also contribute to neuroblastoma tumorigenesis, are loss of heterozygosity (LOH) for chromosome 14 (14q), loss of NF1 and CDKN2A, amplification of DDX1 and MDM2, aberrant expression of neurotrophin receptors, ganglioside GD2, polycomb complex protein Bmi-1, micro RNAs (miR-10b, miR-29a/b, miR-335), as well as mutations in PHOX2B, ATRX, CHEK2 and BARD1 (53,(69)(70)(71)(72)(73)(74)(75)(76)(77).…”
mentioning
confidence: 99%
“…MYCN is involved in cell proliferation, apoptosis, survival and differentiation (62). Neuroblastoma models in which MYCN is overexpressed in the neural crest lead to neuroblastoma tumor development, that is accelerated by cooperation with other oncogenes and tumor suppressor genes, such as ALK, NF1, TP53, LIN28B and LMO1, driving increased penetrance and earlier onset of neuroblastoma (63)(64)(65)(66)(67)(68). Other factors, which also contribute to neuroblastoma tumorigenesis, are loss of heterozygosity (LOH) for chromosome 14 (14q), loss of NF1 and CDKN2A, amplification of DDX1 and MDM2, aberrant expression of neurotrophin receptors, ganglioside GD2, polycomb complex protein Bmi-1, micro RNAs (miR-10b, miR-29a/b, miR-335), as well as mutations in PHOX2B, ATRX, CHEK2 and BARD1 (53,(69)(70)(71)(72)(73)(74)(75)(76)(77).…”
mentioning
confidence: 99%
“…Similarly, in the prostate adenocarcinoma model initiated by Pten mutation, further loss of Rb1 leads to metastasis formation (Ku et al, 2017). Using a genome-wide association study (GWAS) approach, Zhu et al (2017) found that expression of LIM-domain-only gene ( LMO1 ) in a zebrafish model promoted metastatic neuroblastoma driven by the MYCN oncogene. Together, these studies suggest that cooperation of multiple genomic variations could promote the metastatic abilities of tumor cells.…”
Section: Genetics and Genomics Of Metastatic Tumor Cellsmentioning
confidence: 99%
“…Delloye-Bourgeois et al highlight the considerable power of the chick embryo model for neuroblastoma. Zhu and colleagues have also shown that they can model metastasis in zebrafish, where overexpressing the transcriptional regulators LMO1 and MYCN led to metastatic spread (Zhu et al, 2017). These non-mammalian vertebrate models are already improving our understanding of metastatic neuroblastoma, and have potential to identify candidate targets for future clinical trials.…”
Section: Previewmentioning
confidence: 99%